Southern Agricultural Communications Undergraduate Programs: A Survey - Randy Weckman; Deborah Witham; Ricky Telg (Journal of Applied Communications, 2000)
Student enrollment in agricultural communications undergraduate programs continues to increase throughout the southern region. This research reports on a survey of the nine agricultural communications programs in the 13-state southern region. The survey reviewed programmatic areas being taught, the number of students enrolled at each of the institutions, the faculty allocated to the effort, and faculty opinions about the future directions of their programs, especially in terms of enrollment and support for the program. Findings include that all programs depend on a small number of faculty to teach courses; and many of those faculty seem frustrated with a low level of support, recognition and respect. Two-thirds of respondents believed that a national accreditation program would be beneficial to their programs.